Self-Efficacy, Self-Confidence, Achievement Motivation, and Its Relationship Towards Competitive Anxiety - Akhmad Fajri Widodo; Heny Setyawati; Tandiyo Rahayu; Donny Wira Yudha Kusuma; Rafikoh Rafikoh; Iftitakhur Rohmah; Chien-Wei Chen (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Psychological factors play an important role in improving athletes’ competitiveness and personal development. One of the most common conditions athletes experiences during matches is competitive anxiety. In this study we examined the relationship between competitive anxiety and psychological factors such as self-efficacy, self-confidence, and achievement motivation in futsal players. In this cross-sectional study we enrolled 40 participants (30 male and 10 female) from the UFO Star Abadi Futsal Wonosobo team. We used the General Self-Efficacy Scale–Schwarzer (GSES), Sports Confidence Questionnaire, Sports Achievement Motivation Test (SAMT), and Competitive State Anxiety Inventory-2 (CSAI-2) to collect data. Path analysis showed that self-efficacy and self-confidence were significantly correlated with achievement motivation (p < 0.05). Achievement motivation was also significantly correlated with competitive anxiety (p < 0.05). Self-efficacy and self-confidence had direct (p = 0.146 and p = 0.154, respectively) and indirect (p = 0.188 and 0.231, respectively) effects on competitive anxiety. This indicates that both self-efficacy and self-confidence had an indirect effect on the relationship between competitive anxiety and achievement motivation. Improving futsal athletes’ levels of self-efficacy, self-confidence, and achievement motivation would thus help to reduce their competitive anxiety.